Pre-Displacement Psychosocial Well-being Among Planned Displacement: The Perspectives of Msimbazi Basin Residents in Dar es Salaam, Tanzania - Paskal Mbatta, Ignasia (Tanzania Journal for Population studies and Development, 2025)
Over the past few decades, development-induced displacements have become increasingly prevalent across developing countries, including Tanzania. However, the psychosocial impacts of these displacements remain under- explored in academic discourse. This article investigates the lived experiences of communities facing planned displacement in the Msimbazi River Basin, employing Cernea’s impoverishment risks and reconstruction (IRR) model as a theoretical framework. Data was collected in October 2023 through an exploratory qualitative design, incorporating in-depth individual interviews with key informants, focus group discussions, documentary reviews, and field observations. The findings reveal that, in the absence of a comprehensive resettlement plan and adequate compensation, planned forced displacement significantly undermines the psychosocial well-being of the affected. It dismantles traditional modes of production, fractures social networks, erodes cultural identity; and compromises livelihoods, homes, and environments attuned to residents’ skills and practices. These disruptions foster a profound sense of loss and dislocation, heightening the risk of mental health challenges and deepening impoverishment among displaced populations. The article concludes by emphasizing the critical need for inclusive planning processes in development projects. Ensuring community participation, fair compensation, structured resettlement, and accessible psychosocial support are imperative to mitigate the long-term adverse effects of displacement, and to uphold human dignity.